If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 172 = 172 + 4x Add '-172' to each side of the equation. 172 + -172 = 172 + -172 + 4x Combine like terms: 172 + -172 = 0 0 = 172 + -172 + 4x Combine like terms: 172 + -172 = 0 0 = 0 + 4x 0 = 4x Solving 0 = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 0 + -4x = 4x + -4x Remove the zero: -4x = 4x + -4x Combine like terms: 4x + -4x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 2(2x-3)+2=4x-5+2x-3 | | (11-s)=24 | | 2(7x-8)=6(3x-4) | | 3x+9=5(x+3)-2x | | -12=y/3 | | 3x^2+9-24=0 | | 10(-3b+3)=-1+(b+2) | | C/4-4-7.2 | | xy-6x+5y-30= | | F(x)=x^6-5x^3-7 | | 4xy+4y-y^2=0 | | f(x)=-0.3(0.5)x | | 2=2(f+8) | | 3(c+-5)=-9 | | 13x+7-25=13 | | 10x+19-4+12=3 | | -14m+11m=15 | | 14x-9+3-6=11 | | 9y-13=2-8y | | 7-15x+2=14 | | 13+3x-5=20 | | 2(2q+3)=18 | | 5x-3+20=2 | | 8x-(-16)=46-7x | | 8r+r=9 | | 37+7x=9 | | 4t+-13t=18 | | -1.4(-5x-3)-4.3x= | | -128x=46-7x | | -13-4+9= | | -m-17m=0 | | 22=-6+7x |